Determinants of mother to child transmission of HIV among HIV exposed infants managed in Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria - Mairo, Hassan; A., Panti A.; A., Tunau K.; S., Nasir; T., Burodo A.; A., Adamu N.; A., Garba J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Mother to child transmission of HIV (MTCT) is globally known to be the major route of spread of HIV to the unborn fetus and neonate. Many factors related to the mother, infant or the type of HIV virus interplay to increase the risk of MTCT of the virus. Antepartum antiretroviral drugs administration reduces the maternal viral load therefore lowering the risk of transmission. The objective is to determine infection rate and assess determinants of MTCT of HIV exposed infants delivered in UDUTH Sokoto. Methods: It was a 5-year retrospective study. Records of all HIV positive pregnant women and their babies managed in UDUTH were reviewed from the E health system of the hospital. Patient’s details were recorded from booking to delivery for the period under study. The infant’s records were retrieved and information from delivery to 18 months post-delivery obtained. Structured data collection tool was developed to compile the required information. Data was analyzed using SPSS IBMS 22. Descriptive statistics and comparisons between variables were made statistically using Chi square. P value of ≤ 0.005 was considered as significant. Results: Records of all the patients recruited were all available for evaluation because authors use the E-health system of records keeping in our hospital. MTCT rate was 0.92%. Majority 60 (47.2%) were within age group 26-30yrs. The subjects were predominantly house wives 97(71.4%) and multipara 77 (60.6%). Viral load ranged between 112 to 28228 copies/ml. Twenty-two (17.3%) had CD4 count less than 250 cells/µl while 61 (48%) had counts above 500cells/µl. All were in WHO clinical stage 1-3. All were on triple regimen anti-retroviral drugs. Spontaneous rupture of membranes for over 4 hours occurred in 51(32%). Vaginal delivery was recorded in 89.7%. Breast feeding was practiced by 48%. Conclusions: Breast-feeding still remains a risk factor for MTCT OF HIV Early administration of maternal antiretroviral drugs significantly reduces the rate of mother to child transmission of HIV.